Lipase activity of fungal isolates from the surface of green pineapple (Ananas Comosus) - Mendoza, Joy C. (2006)
ABSTRACT Fungal isolates were obtained from the surface of fresh 'Queen' pineapple and were subjected to qualitative and quantitative screening for lipase activity. Out of 21 isolated fungi, 11 were positive for lipase activity using Tween 20 and 6 were positive for lipase activity using Tween 80 as substrate. These positive fungal isolates were further subjected to quantitative screening using the titrimetric method. The qualitative tests showed a significant difference in lipase activity when the two substrates were used, and provides confirmation that Tween 20 is a better lipase substrate compared to Tween 80. Although fungi with lipase activity could be isolated from pineapple, the use of the fungicide, Amistar^TM, effected a control of lipolytic action. Pineapple fruits coated with an emulsion of coconut oil and Amistar did not develop the aroma associated with coconut oil that has undergone hydrolysis. This improves the favorable effect of coconut oil in extending the shelf life of pineapples. Treated pineapples, however, still showed signs of fermentation associated with yeasty rot.